Model Peningkatan Aktivitas Belajar Melalui Strategi Everyone Is A Teacher Here Kombinasi Answer Gallery Dalam Proses Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan Pada Siswa Kelas VII A SMP Muhammadiyah 5 Surakarta Tahun Pelajaran 2015/2016 - Yuliawati, Aninda Lilis, Drs. Achmad Muthali'in, M.Si (2016)
This study aims to improve the learning activities in the learning process Pancasila and Civics Education students of class VII A grade Student Junior High School of Muhammadiyah 5 Surakarta 2015/2016 academic year through strategies Everyone is a Teacher Here combinatied with Answers Gallery. The Learning activities of the students was very low before the test models and teachers has been alternative the solutions, such as: use of discussions, lectures, and question and answer. The through results the application of learning strategy has not been able to improve student learning activities. The solution offered in this study is a model of increased activity learns through strategies Everyone is a Teacher Here combinatied with Answers Gallery. The subjects were students of class VII A grade Junior High School of Muhammadiyah 5 Surakarta 2015/2016 totaling 28 learners. Data were collected through informants and resource persons, the places and then events of the ongoing activities of the learning process. The collection data techniques by using the method of observation, interviews and documentation. The development procedure in this research through several stages of designing a model of learning, planning, implementation, and evaluation and improvement. This research was conducted through two models test. Expected through strategy Everyone is a Teacher Here combinatied of Answers Gallery learning activities in the learning process Pancasila and Civics Education students of class VII A grade Student Junior High School of Muhammadiyah 5 Surakarta 2015/2016 can be increased by at least 80% of 28 students. The results of this study shows that the learning activity at class VII A SMP Muhammadiyah 5 Surakarta 2015/2016 academic year prior research conducted through strategic Everyone is a Teacher Here combinatied with Answers Gallery are as many as 7 children (25%). After the model testing is through a strategy Everyone is a Teacher Here combinatied with Answers Gallery, the trial model I increased to 12 students (42.86%) and the model II trials increased to 25 students (89.28%). Keywords: Strategies Everyone is a Teacher Here combination of Answers Gallery, Learning Activities, Learning Process Pancasila and Civics Education.